Survival of an Enveloped Virus on Toys. Issue 8 (August 2016) - Bearden, Richard L.; Casanova, Lisa M.
Abstract : Children's toys may carry respiratory viruses. Inactivation of a lipid-enveloped bacteriophage, Φ6, was measured on a nonporous toy at indoor temperature and relative humidity (RH). Inactivation was approximately 2log10 after 24 hours at 60% RH and 6.8log10 at 10 hours at 40% RH. Enveloped viruses can potentially survive on toys long enough to result in exposures.